Media Convergence as Evolutionary Process - Lugmayr, Artur; Dal Zotto, C. (Springer-Verlag Heidelberg, 2016)
Within this chapter, we address convergence as matter of evolutionary process. Key terminology is introduced and discussed, and provide a critical overview of the phenomenon of convergence. This chapter presents several key-ideas existing in literature around the thematic area of convergence, and provides insights concerning the media convergence process. We contribute to the media study debate about causes and effects of the media evolution process by highlighting trends and gaps in research and in the overall field of media convergence. The chapter rounds up with a discussion of the different book chapters, and their contribution to the field. We see this chapter as an introduction chapter for readers that want to understand the phenomenon of convergence.